Quantitative analysis of constitutions - Jerg Gutmann; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2022)
Since the time of the Protestant reformation, Western societies typically consider themselves not to be governed by divine law but based on a social contract. While all rules governing a society are part of this social contract, a country's written constitution is a central and possibly the most important manifestation of the social contract. Once it is accepted that the contents of a constitution are subject to human design, scholars interested in the organization of human societies will ask themselves how constitutions should look like. Or less normatively speaking, the question arises what consequences can be expected from the design of different elements of a constitution. For a long time, (comparative) constitutional legal scholars have tried to evaluate the consequences of constitutional design by drawing on and comparing select country cases. Such a qualitative empirical research approach, however, has its limitations. While it might be suitable to generate theories of how constitutions work, it is difficult to assess whether these explanations are valid when applied to a larger set of constitutions (i.e., whether findings from a single or few countries can be generalized) and whether one theory potentially outperforms other theories in explaining differences across countries and time. Thanks to the ever-increasing availability of sophisticated statistics software, powerful personal computers, and well-trained researchers, quantitative analyses of constitutions have surged in recent decades. (...)
Keywords: 330